Inorganic Nanomaterials for Supercapacitor Design - Inamuddin, 1980-; Boddula, Rajender; Ahmer, Mohammad Faraz; Asiri, Abdullah M. (Milton : CRC Press LLC, 2020)
Among electrode materials, inorganic materials have received vast consideration owing to their redox chemistry, chemical stability, high electrochemical performance, and high-power applications. These exceptional properties enable inorganic-based materials to find application in high-performance energy conversion and storage. The current advances in nanotechnology have uncovered novel inorganic materials by various strategies and their different morphological features may serve as a rule for future supercapacitor electrode design for efficient supercapacitor performance. Inorganic Nanomaterials for Supercapacitor Design depicts the latest advances in inorganic nanomaterials for supercapacitor energy storage devices. Key Features: Provides an overview on the supercapacitor application of inorganic-based materials. Describes the fundamental aspects, key factors, advantages, and challenges of inorganic supercapacitors. Presents up-to-date coverage of the large, rapidly growing, and complex literature on inorganic supercapacitors. Surveys current applications in supercapacitor energy storage. Explores the new aspects of inorganic materials and next-generation supercapacitor systems.
Chapter 16: Amino Acid-Assisted Inorganic Materials for Supercapacitors -- Chapter 17: Co-Based Materials for Supercapacitors -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Supercapacitors -- Design; Nanostructured materials; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Material Science